Clinical epidemiological characteristics of the acute diarrheal disease due to Vibrio cholerae in patients up to 10 years - Josefina Herrera López; Camila Valverde Ramón; Frank Emilio Escobedo Batista; Eduardo Hodelín Pozo; María Elena Mora Arias (Centro Provincial de Información de Ciencias Médicas, 2018)
An observational, descriptive and cross-sectional investigation of 95 children aged 0 to 10, with diagnosis of acute diarrheal disease due to  Vibrio cholerae, assisted in "Dr. Juan de la Cruz Martínez Maceira" Northern Children Hospital in Santiago de Cuba, was carried out during  2016, in order to characterize them according to some clinical and epidemiological variables.  Among the predominant results there were the 0 to 11 months age group as the most affected and the presence of a higher number of cases in Santiago de Cuba municipality, that corresponded mainly to the health areas of "Frank País García", "José Martí Pérez" and "Josué País García" polyclinics.  Also it was evidenced that the main manifestation of the infectious process was the liquid diarrhea and the most frequent complication, the moderate isotonic dehydration.  None of the children died, which demonstrates the effectiveness of medical care in the southeastern territory of Cuba.